RASIONALISME DAN MODERNITAS ISLAM DALAM PRESPEKTIF TAFSIR AL-MIZAN - Muhammad Said (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2026)
This paper examines the role of rationalism in Tafs?r al-M?z?n f? Tafs?r al-Qur’?n by All?mah Muhammad Husayn al-?ab??ab??? and its contribution to the formation of Islamic modernity. Departing from the epistemological crisis in contemporary Islamic thought—marked by tension between literalistic textualism and modern rationality—this study emphasizes the urgency of integrating reason and revelation within Qur’anic exegesis. Employing a qualitative library research approach with content analysis, this study analyzes al-?ab??ab???’s works alongside relevant secondary literature. The findings reveal that rationalism in Tafs?r al-M?z?n functions as an epistemological paradigm that positions reason as a primary hermeneutical instrument while maintaining the authority of revelation. Through the method of interpreting the Qur’an by the Qur’an (bil-Qur’?n bi al-Qur’?n), rational ta’w?l, and philosophical reflection, al-?ab??ab??? establishes a synthesis between classical Islamic intellectual tradition and the demands of modernity. This rationalist approach contributes to the construction of an Islamic modernity that is inclusive, ethical, and responsive to contemporary issues such as pluralism, social ethics, and the relationship between religion and science. Thus, Tafs?r al-M?z?n represents a model of Islamic modernity rooted in revelation, guided by rationality, and oriented toward spiritual and social transformation.